IoT as an aggregator for industry and customer: A conceptual model - Bhushan, A.Vinay (IJRDO -Journal of Computer Science Engineering, 2018)
Suppose if we ask common public on the street to define the term, “The Internet of Things “ and you will get a curious look to you with a big question mark on their face. Although many people don’t use the term "Internet of Things (IoT)", but most of them might have experienced the IoT with smartphones, tablets, and PCs which they already use on a regular basis. Internet and smart phone users’ penetration has been increasing in last four years. A report by IAMAI and KPMG projected that India will reach 236 million mobile internet users by 2016, and 314 million by 2017. There is a huge business opportunity for e- commerce industries to connect to their customers and prospective customers in real time. Even other industries concentrating on making near connect using IOT with Internet and smart phones, has changed dimensions of businesses and created new innovative markets and its approach. The everyday physical objects that could be connected through the IoT run from the simple and mundane. By 2018, Internet of Things (IoT) number will reach 9 billion, which is from combinations of smartphones, tablets, PCs, wearable computers, smart TVs and machines. Today, IoT produces about 1 trillion (£600 billion) in revenue, and that figure is expected to double by 2016. The Internet of Things, like big data, is creating an impact across industries, because every industry is becoming virtual and is progressing towards a device or product that can be further utilized to boost profits or cut costs. Only one mobile device has created the 10.7 Billion sales in 2014. If mobile devices are connected with multiple devices nearby and could communicate with each other informatively then the vibration of this kind of exchange of information can create multiple business opportunities and revenue. This research leads to designing a model for an industry’s opportunity where IoT can added advantage for industries to understand better and serve their customer using Internet, IPV6, smart phone and sensors. These are interconnected in such a way that the information mutually transmitted can create a better value proportion by identifying the untouched, untapped, un-attended information about consumer or customer about the industry or its products in real time. Tapping this gap can lead to add-on to the current business without spending much time and money. This ease of information making available will be beneficiary to the customer and marketers where they can get the information or details of anything related to product or service will be in a fingertip. The study is targeting a conceptual Eco-model which is expected to attain seamless information exchange where both the parties (marketer and buyers) can be looking at mutual services which can maximize their benefits.